Pengaruh Motivasi Kerja, Perencanaan Karier, dan Efikasi Diri terhadap Kesiapan Kerja Mahasiswa FEB Universitas Bhayangkara Jakarta Raya - Laili Dian Safitri; Yayan Hendayana; Sri Wulandari (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of work motivation, career planning, and self-efficacy on work readiness among students at the Faculty of Economics and Business, Bhayangkara Jakarta Raya University. The research is motivated by the rising unemployment rate among university graduates and low student work readiness identified through a preliminary survey. This study uses a quantitative causal approach with a population of active 2022 students from the Management and Accounting study programs. The sample consisted of 200 respondents selected using proportional cluster sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS 26. The results show that work motivation has a positive and significant effect on work readiness (t-value 4.193; sig. 0.000). Career planning has a positive and significant effect (t-value 3.529; sig. 0.001). Self-efficacy has a positive and significant effect with the most dominant influence (t-value 6.778; sig. 0.000). Simultaneously, the three variables significantly affect work readiness (F-value 87.558; sig. 0.000) with a contribution of 57.3% (R²=0.573), while the remaining 42.7% is influenced by other factors outside the model.